Representation of the Croatian National Revival and Romanticism in Croatian Literary Historiography - Coha, Suzana (Poznańskie Studia Slawistyczne, 2023)
The paper presents poetically and politically conditioned changes in the interpretation of the literature of the Croatian National Revival period as “Romantic”. It indicates that these phenomena should necessarily be viewed in mutual (inter) action. It states that the Croatian National Revival, as a period that is most frequently demarcated by the years 1835 and 1848–49 in the so-called general historiography, is a necessary framework for the periodisation and understanding of the history of Croatian literature too. This framework does not exclude the necessity of including the concept of Romanticism in the study of Croatian literature of this period, which was strongly influenced by Romantic trends. And consequently it is a stage in a longer period of manifestation of Romantic features in Croatian culture and literature of the 19th century.